2018
DOI: 10.1002/adfm.201706927
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Crystallite Kinetics in Homogenous Bilayer Oxide Memristor for Emulating Diverse Synaptic Plasticity

Abstract: A critical routine for memristors applied to neuromorphic computing is to approximate synaptic dynamic behaviors as closely as possible. A type of homogenous bilayer memristor with a structure of W/HfO y /HfO x /Pt is designed and constructed in this paper. The memristor replicates the structure and oxygen vacancy (V O ) distribution of a complete synapse and its Ca 2+ distribution, respectively, after the forming process. The detailed characterizations of its atomic structure and phase transformation in and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 55 publications
(73 reference statements)
4
116
0
1
Order By: Relevance
“…The left part of Figure d presents the conductance variation of A‐RS. The device conductance is strengthened/weakened continuously by 50 consecutive positive/negative voltage pulses, which can simulate the synaptic potentiation/depression process when treating the device conductance as the synapse weight . The right part of Figure d shows the conductance variation of D‐RS, in which the reversible switching between LCS and HCS is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The left part of Figure d presents the conductance variation of A‐RS. The device conductance is strengthened/weakened continuously by 50 consecutive positive/negative voltage pulses, which can simulate the synaptic potentiation/depression process when treating the device conductance as the synapse weight . The right part of Figure d shows the conductance variation of D‐RS, in which the reversible switching between LCS and HCS is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…PTP acts on a longer time scale of tens of seconds to minutes. [92,99,118,[176][177][178][179] By varying the time interval between the paired pulses, the amplitude of EPSC caused by the second pulse can be tuned; generally, a longer interval results in a reduced EPSC amplitude enhancement. It is associated with Ca 2+ dependent activation of presynaptic protein kinases.…”
Section: Short-term Synaptic Plasticity (Stsp)mentioning
confidence: 99%
“…The original form of Hebbian learning did not include LTD. CMOS devices, [162] CBRAM, [99] RRAM, [179] hybrid CMOS/RRAM, [224] perovskite devices, [225] and many others have been employed to show SRDP in response to incoming pulses at different frequencies: a high-frequency (20-100 Hz) train of presynaptic pulses results in LTP of the synaptic strength, whereas a low-frequency (1-5 Hz) train results in LTD. [223] SRDP is a terminology used in the field of electronics rather than neuroscience to describe these rules.…”
Section: Hebbian Learningmentioning
confidence: 99%
“…Yin et al reported a bilayer memristor with a W/HfO y /HfO x /Pt structure which replicates the Ca 2+ distribution in biological synapse. Both EPSC and IPSC response were mimicked exhibiting a current relaxation.…”
Section: Ionotronic Memristorsmentioning
confidence: 99%